Turning Automotive Windows into the Ultimate HMIs. (22nd July 2020) - Firth, Michael
Abstract: New technologies promise to transform vehicles' windows into bright, vivid, full‐motion video‐capable displays. Here, we take a closer look at the potential applications and trends in window displays and how they'll change the driving experience.